PKA phosphorylation of NCLX reverses mitochondrial calcium overload and depolarization, promoting survival of PINK1-deficient dopaminergic neurons - Kostic, Marko; Ludtmann, Marthe H. R.; Bading, Hilmar; Hershfinkel, Michal; Steer, Erin; Chu, Charleen T.; Abramov, Andrey Y.; Sekler, Israel (Cell reports, 2015)
Mitochondrial Ca2+ overload is a critical, preceding event in neuronal damage encountered during neurodegenerative and ischemic insults. We found that loss of PTEN-induced putative kinase 1 (PINK1) function, implicated in Parkinson disease, inhibits the mitochondrial Na+/Ca2+ exchanger (NCLX), leading to impaired mitochondrial Ca2+ extrusion. NCLX activity was, however, fully rescued by activation of the protein kinase A (PKA) pathway. We further show that PKA rescues NCLX activity by phosphorylating serine 258, a putative regulatory NCLX site. Remarkably, a constitutively active phosphomimetic mutant of NCLX (NCLXS258D) prevents mitochondrial Ca2+ overload and mitochondrial depolarization in PINK1 knockout neurons, thereby enhancing neuronal survival. Our results identify an mitochondrial Ca2+ transport regulatory pathway that protects against mitochondrial Ca2+ overload. Because mitochondrial Ca2+ dyshomeostasis is a prominent feature of multiple disorders, the link between NCLX and PKA may offer a therapeutic target.